Ahmad Bin Hanbal's Educational Thoughts - Hendra Sudrajat; Syahidin; Iswandi, Iswandi (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2026)
This article aims to examine the educational thought of Imam Ahmad ibn Hanbal, a prominent figure in Islamic history known as a hadith scholar and founder of the Hanbali school of thought. Although better known in the fields of hadith and fiqh, the educational aspect of his thought is often overlooked. This study uses a qualitative approach by analyzing literature related to the educational values ​​of monotheism taught by Imam Ahmad. The analysis shows that monotheism education, according to Imam Ahmad, is a process of instilling belief in the oneness of Allah SWT, which must begin at an early age. The three main values ​​of Imam Ahmad's monotheism education encompass a Muslim's behavior in relation to Allah, oneself, and fellow human beings. This emphasis on monotheism education reflects Imam Ahmad's commitment to the pure teachings of Islam and the importance of educating the younger generation on a strong foundation of faith. Keywords: Educational Thought, Monotheism, Imam Ahmad ibn Hanbal.